Epitaxial growth of n-type _-FeSi2 thin films on p-type Si(111) substrates by radio-frequency magnetron sputtering and rectifying action of heterojunctions - Tarek M. Mostafa; Motoki Takahara; Ryuji Baba; Suguru Funasaki; Mahmoud Shaban; Nathaporn Promros; Aki Tominaga; Maiko Nishibori; Tsuyoshi Yoshitake (My University, 2015)
n-Type β-FeSi2 thin films were deposited on p-type Si(111) substrates by conventional radio frequency magnetron sputtering at substrate temperatures of 500–600 °C without post-annealing. The epitaxial growth of β-FeSi2 on Si(111) initiates at substrate temperatures of higher than 560 °C, and it was found that the epitaxial growth is indispensable for the n-type β-FeSi2/p-type Si heterojunctions having rectifying action.
Keywords: Cavity magnetron; Semiconductor materials and interfaces